2019
DOI: 10.1002/ehf2.12429
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal skeletal muscle mass as a predictor of mortality in Japanese patients undergoing left ventricular assist device implantation

Abstract: Aims We assessed preoperative muscle wasting in patients undergoing left ventricular assist device (LVAD) implantations using abdominal skeletal muscle images on computed tomography (CT) and explored the associations between the preoperative muscle wasting and clinical outcomes after LVAD implantation. Methods and results We retrospectively examined the records of 111 patients who underwent continuous‐flow LVAD implantations as bridge‐to‐transplant therapy from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…25 Thus, even though these authors identified low psoas muscle area in patients with chronic HF after an acute hospitalization as an independent predictor of death, these findings should not be extrapolated to the skeletal muscle mass of the extremities. Very similarly, Tsuji et al 5 examined psoas muscle mass in 78 patients undergoing left ventricular assist device implantation. They found that perioperative muscle wasting as extrapolated from the psoas measurement approach was associated with higher mortality in their patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Thus, even though these authors identified low psoas muscle area in patients with chronic HF after an acute hospitalization as an independent predictor of death, these findings should not be extrapolated to the skeletal muscle mass of the extremities. Very similarly, Tsuji et al 5 examined psoas muscle mass in 78 patients undergoing left ventricular assist device implantation. They found that perioperative muscle wasting as extrapolated from the psoas measurement approach was associated with higher mortality in their patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The large range mirrors the association with the cohort under investigation. For example, stable ambulatory patients seem to have lower prevalence values than patients with acute or advanced HF, [5][6][7] and patients with dilated cardiomyopathy may have higher prevalence values than patients with ischaemic heart disease. 2,3,8 It is important to note that skeletal muscle wasting, in geriatric populations commonly called sarcopenia, is different from cachexia, because only cachexia is by definition associated with weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a quantitative assessment of the cross-sectional muscle area using computed tomography (CT) images is available to assess changes in skeletal muscle mass [14]. This assessment calculates the skeletal muscle index (SMI) (cm 2 /m 2 ) by dividing the cross-sectional area (cm 2 ) of the skeletal muscle at the level of the third lumbar vertebra (L3) by the square of the patient’s height (m 2 ) on CT [15]. SMI measured using CT may reflect MRC scores.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle wasting is one of the main causes for exercise intolerance and ventilatory inefficiency in HF patients [57]. It promotes the aggravation of other clinical conditions and causes a deterioration of quality of life [58]. It is associated with a longer hospital stay [59], more frequent re-hospitalizations [60], and worsened prognosis [61].…”
Section: Sarcopenia In Hfmentioning
confidence: 99%